The Significance of Lingua-Methodical Experiences in the Preparation of Activities of the Foreign Language Teacher (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Forming lingua-methodical experiences on EFL students in higher education system is related with the image of identification, readiness for transferring the identity and undoubtedly teaching system. Linguistic-methodical experience is a psychological renewal, which includes cognitive and behavioral aspects, as well as a long-term state of preparation directly related to professional activity as an integrative feature of a person.